2020
DOI: 10.1016/j.rse.2019.111627
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation retrieval from Landsat optical/thermal data integrated into a crop water balance model: A case study over winter wheat fields in a semi-arid region

Abstract: Monitoring irrigation is essential for an efficient management of water resources in arid and semi-arid regions. We propose to estimate the timing and the amount of irrigation throughout the agricultural season using optical and thermal Landsat-7/8 data. The approach is implemented in four steps: i) partitioning the Landsat land surface temperature (LST) to derive the crop water stress coefficient (Ks), ii) estimating the daily root zone soil moisture (RZSM) from the integration of Landsat-derived Ks into a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 66 publications
1
36
0
1
Order By: Relevance
“…Lower, but still significant, errors (RMSE of 44 mm relative to actual mean water use of 245 mm) are reported by Olivera‐Guerra et al (2020) for five plots over two to four seasons using a thermal‐infrared‐based model. Olivera‐Guerra et al (2020) focus on wheat production in Morocco where precipitation and cloud cover are minimal and use validation data from experimental plots, showing that uncertainty in water use estimation remains significant even if it is possible to reduce errors introduced by input data uncertainty or unobserved heterogeneity in farmer irrigation management practices.…”
Section: Uncertainty In Satellite‐based Water Use Estimatesmentioning
confidence: 63%
See 2 more Smart Citations
“…Lower, but still significant, errors (RMSE of 44 mm relative to actual mean water use of 245 mm) are reported by Olivera‐Guerra et al (2020) for five plots over two to four seasons using a thermal‐infrared‐based model. Olivera‐Guerra et al (2020) focus on wheat production in Morocco where precipitation and cloud cover are minimal and use validation data from experimental plots, showing that uncertainty in water use estimation remains significant even if it is possible to reduce errors introduced by input data uncertainty or unobserved heterogeneity in farmer irrigation management practices.…”
Section: Uncertainty In Satellite‐based Water Use Estimatesmentioning
confidence: 63%
“…Garrido-Rubio et al ( 2020) report plot-level root-mean-square error (RMSE) in irrigation water use by crop type ranging from 44-176 mm (6-77% of actual water use), while Battude et al ( 2017) report RMSE's of 32-60 mm (19-35% of actual water use) at field levels even when averaging estimates over several years. Lower, but still significant, errors (RMSE of 44 mm relative to actual mean water use of 245 mm) are reported by Olivera-Guerra et al (2020) for five plots over two to four seasons using a thermal-infrared-based model. Olivera-Guerra et al (2020) focus on wheat production in Morocco where precipitation and cloud cover are minimal and use validation data from experimental plots, showing that uncertainty in water use estimation remains significant even if it is possible to reduce errors introduced by input data uncertainty or unobserved heterogeneity in farmer irrigation management practices.…”
Section: Model Validation and Uncertaintiesmentioning
confidence: 84%
See 1 more Smart Citation
“…In another study of Ras Ghareb city in Egypt, Sentinel-2 data and fuzzy analytic hierarchy process approaches were also used for monitoring and assessing urban flash flood impacts [208]. In their case study of winter wheat fields in a semi-arid region, Olivera-Guerra et al [209] showed irrigation retrieval from Landsat optical and thermal data integrated into a crop water balance model.…”
Section: Flood Events and Floodplain Risksmentioning
confidence: 99%
“…For this reason, many studies have been carried out to evaluate agricultural drought severity using remote sensing data or soil moisture analysis models [8][9][10][11][12][13][14][15][16][17]. In the case of study using remote sensing data, the drought was evaluated using soil moisture, vegetation activity, and land surface temperature data, which are used to monitor agricultural droughts [8][9][10][11][12]. These studies have the advantage of overcoming the spatial limitation of ground observation data, but there are limitations such as image acquisition frequency, sensor-specific errors, and uncertainty of specific algorithms.…”
Section: Introductionmentioning
confidence: 99%